Fructans and Mineral Nutrition - Benkeblia, Noureddine (Journal of Nutritional Therapeutics, 2016)
Fructan molecules have a history of more than 150 years and ancient peoples used fructans containing plants as food, feed or medicine. The modern history of fructans began with their discovery by Rose (1804) and known at the turn of the 20th century considerable development with Edelman's proposal concerning their metabolism in higher plant. At present time, fructans are considered food not food ingredients, and are found in more than 500 food products resulting in significant daily consumption. Because the science of nutrition itself has changed, fructans are now considered as functional foods and the passionate history of their health benefits continues to arise interest of scientists. Contrary to the fact that non-digestible carbohydrates have been accused of causing an impairment in the small intestine absorption of minerals, research conducted during the last three decades demonstrated that fructans enhanced mineral absorption, and the scientific evidence claiming that fructans enhance mineral absorption is based on both animal and human experiments which are very conclusive. Although different hypotheses have been proposed to explain the roles of fructans in enhancing minerals absorption, the mechanisms behind this enhancement are still unclear, even though investigation have demonstrated that different fructans-related mechanisms may be involved in the increased absorption of minerals due to fructans intake. This review paper aims to report on the recent development and the roles of fructans in enhancing mineral absorption and their deficiencies prevention.